Exploring Factors Influencing Low Back Pain in People With Nondysvascular Lower Limb Amputation: A National Survey. Issue 10 (2nd March 2017) - Devan, Hemakumar; Hendrick, Paul; Hale, Leigh; Carman, Allan; Dillon, Michael P.; Ribeiro, Daniel Cury
Abstract: Background: Chronic low back pain (LBP) is a common musculoskeletal impairment in people with lower limb amputation. Given the multifactorial nature of LBP, exploring the factors influencing the presence and intensity of LBP is warranted. Objective: To investigate which physical, personal, and amputee‐specific factors predicted the presence and intensity of LBP in persons with nondysvascular transfemoral amputation (TFA) and transtibial amputation (TTA). Design: A retrospective cross‐sectional survey. Setting: A national random sample of people with nondysvascular TFA and TTA. Participants: Participants (N = 526) with unilateral TFA and TTA due to nondysvascular etiology (ie, trauma, tumors, and congenital causes) and a minimum prosthesis use of 1 year since amputation were invited to participate in the survey. The data from 208 participants (43.4% response rate) were used for multivariate regression analysis. Methods (Independent Variables): Personal (ie, age, body mass, gender, work status, and presence of comorbid conditions), amputee‐specific (ie, level of amputation, years of prosthesis use, presence of phantom‐limb pain, residual‐limb problems, and nonamputated limb pain), and physical factors (ie, pain‐provoking postures including standing, bending, lifting, walking, sitting, sit‐to‐stand, and climbing stairs). Main Outcome Measures (Dependent Variables): LBP presence and intensity. Results: A multivariate logistic regression model showed that the presence of 2 or more comorbid conditions (prevalence odds ratio [POR] = 4.34, P = .01), residual‐limb problems (POR = 3.76, P < .01), and phantom‐limb pain (POR = 2.46, P = .01) influenced the presence of LBP. Given the high LBP prevalence (63%) in the study, there is a tendency for overestimation of POR, and the results must be interpreted with caution. In those with LBP, the presence of residual‐limb problems (β = 0.21, P = .01) and experiencing LBP symptoms during sit‐to‐stand task (β = 0.22, P = .03) were positively associated with LBP intensity, whereas being employed demonstrated a negative association (β = −0.18, P = .03) in the multivariate linear regression model. Conclusions: Rehabilitation professionals should be cognizant of the influence that comorbid conditions, residual‐limb problems, and phantom pain have on the presence of LBP in people with nondysvascular lower limb amputation. Further prospective studies could investigate the underlying causal mechanisms of LBP. Level of Evidence: II